Diagnosing and managing paediatric concussion: Key recommendations for general paediatricians and family doctors. Issue 7 (20th May 2021) - Dawson, Jennifer; Reed, Nick; Bauman, Shannon; Seguin, Ryan; Zemek, Roger
Abstract: Concussion in children and adolescents is an important health concern. Most paediatric patients fully recover in 1 month or less following an acute concussion. However, some experience prolonged or persistent concussion symptoms for months. Those with prolonged post-concussion-related symptoms may have impaired quality of life, and limited involvement in social, academic, and physical activities with associated mental health implications. In this review, we share key updated clinical recommendations from the Living Guideline for Diagnosing and Managing Pediatric Concussion that will improve the way general paediatricians and family doctors diagnose and manage paediatric patients with suspected concussion.